The voluntary sustainability standards and their contribution towards the achievement of the Sustainable Development Goals: A systematic review on the coffee sector - Karla Rubio-Jovel (Journal of International Development, 2022)
In 2015, the United Nations adopted the Sustainable Development Goals (SDGs). Voluntary sustainability standards (VSSs) precede the SDGs and are a major governance tool for sustainability. Consequently, it is important to understand the role of VSS towards the achievement of the SDGs. This article contributes to answer this question through a systematic review of literature. Results revealed research gaps for key SDGs, such as SDG 5 (Gender Equality) and SDG 10 (Reduced Inequalities). Another relevant finding is that more than half of the studied variables showed no significant difference between intervention or control group, or no significant change over time. This article encourages VSSs and policymakers to work collaboratively towards the use of common indicators and increased data transparency.
Keywords: 300; coffee; data transparency; standard indicators; Sustainable Development Goals; voluntary sustainability standards (VSSs)